2007
DOI: 10.1007/s10266-007-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Bolton's tooth size ratios to a Japanese orthodontic population

Abstract: Previous studies have shown that tooth size ratios are ethnicity-, race-, and sex-specific. This study was carried out to determine anterior and overall ratios in a Japanese population and to compare them with Bolton's ratios. Numerical data were obtained from 60 pairs of dental casts of 30 male and 30 female Japanese orthodontic patients. The mesiodistal widths from first molar to first molar were measured on each cast to the nearest 0.01 mm, by using digital calipers, and the anterior and overall ratios were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 16 publications
5
28
2
5
Order By: Relevance
“…9,12 The amount of SD from the Bolton mean of any measured ratio and the millimetric amount of maxillary and mandibular corrections are used as indicators of clinically significant tooth-size discrepancy. Several studies defined the ratios outside 2 SDs from the Bolton mean as values indicating clinically significant tooth-size discrepancies, [6][7][8]10,11,[13][14][15] while some other studies defined the ratios outside 1 SD from Bolton mean 11,16 because Bolton 3 suggested that a value greater than 1 SD from his mean indicated a possible treatment need. From a clinical perspective, the actual amount of discrepancy expressed in millimeters provides more useful information on the correction for clinically significant tooth-size discrepancy than the ratio in percentage terms.…”
Section: Introductionmentioning
confidence: 99%
“…9,12 The amount of SD from the Bolton mean of any measured ratio and the millimetric amount of maxillary and mandibular corrections are used as indicators of clinically significant tooth-size discrepancy. Several studies defined the ratios outside 2 SDs from the Bolton mean as values indicating clinically significant tooth-size discrepancies, [6][7][8]10,11,[13][14][15] while some other studies defined the ratios outside 1 SD from Bolton mean 11,16 because Bolton 3 suggested that a value greater than 1 SD from his mean indicated a possible treatment need. From a clinical perspective, the actual amount of discrepancy expressed in millimeters provides more useful information on the correction for clinically significant tooth-size discrepancy than the ratio in percentage terms.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies did not report differences in both anterior and overall ratios comparing different populations with Bolton standards 10 . On the other hand, contrasting results were reported by Endo et al 7 (2007), who found anterior and overall ratios from a Japanese population greater than those from Bolton's American population.…”
Section: Discussionmentioning
confidence: 68%
“…The Japanese-Brazilian group showed significantly greater anterior and overall ratios than Bolton standards. Other studies also reported significantly greater anterior ratio 8,7,13,24 and overall ratio 6,13,25 than Bolton standards for different populations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The posterior ratio and overall ratio are also used. Although each of these ratios has been studied extensively for a range of different racial [7][8][9][10] and malocclusion groups, [11][12][13][14][15][16] it is not clear whether their clinical application in these studies was appropriate. To clarify this issue, Tonn specifically analyzed the ratio of the upper and lower premolars.…”
Section: Introductionmentioning
confidence: 99%